Strategic assessment of adverse media in the due diligence process for ESG risk decision-making - Fernandez, Manuel; Rangel-Perez, Celia; Lopez, Belen (Transformations In Business & Economics, 2025)
There is a growing interest in measuring sustainability performance because companies that adhere to ESG criteria (environmental, social and governance criteria) experience higher valuation and better financing conditions. However, recognizing the limitations of voluntary initiatives, the European Union has implemented regulatory measures, exemplified by the impending Corporate Sustainability Due Diligence Directive (CSDDD), aimed at transforming supply chain monitoring within and outside the EU. Using the Banco Santander case, this research assesses the validity of the company’s control framework for ESG issues with a regressive methodology. While the framework incorporates intricate risk information and investment restrictions, it is mainly based on adverse media contrasts and assessments. Despite serving as a valuable source for risk decision-making, adverse media introduces challenges such as inaccuracies, bias, and a lack of contextual understanding. As a result, this research advocates for further analysis, recommending diversified case studies and expanded information sources to strengthen control frameworks.